Analisis Customer Experience, Digital Marketing Terhadap Kepuasan Pelanggan Melalui Konten Live Streaming di PT. Daya Mega Pratama - Putra Maruli Saing; Harianto (Cattleya Darmaya Fortuna, 2026)
This study uses a quantitative approach with a survey method of 97 respondents who are active customers of the company. The data analysis techniques used included multiple linear regression and mediation tests using the Sobel Test with the help of SPSS software. The results showed that Customer Experience did not have a significant effect on Customer Satisfaction (B = 0.085; t = 0.930; Sig. = 0.355), and Digital Marketing also did not have a significant effect on Customer Satisfaction (B = 0.125; t = 1.675; Sig. = 0.097). On the other hand, Live Streaming Content has a positive and significant effect on Customer Satisfaction (B = 0.626; t = 6.479; Sig. = 0.000). The results of the partial test showed that Customer Experience had a positive and significant effect on Live Streaming Content (B = 0.608; t = 8.176; Sig. = 0.000), while Digital Marketing had no significant effect on Live Streaming Content (B = −0.016; t = −0.198; Sig. = 0.844). The results of the mediation test showed that Live Streaming Content significantly mediated the influence of Customer Experience on Customer Satisfaction, but did not mediate the influence of Digital Marketing on Customer Satisfaction. The Adjusted R² value of 0.408 indicates that 40.8% of the variation in Customer Satisfaction can be explained by the study model, while the rest is influenced by other factors outside of this study. These findings confirm that the success of the company's digital strategy in improving Customer Satisfaction relies heavily on optimizing Live Streaming Content, especially in delivering an interactive and informative customer experience.